Patient satisfaction with the perioperative surgical services and associated factors at a University Referral and Teaching Hospital, 2014: a cross-sectional study - Endale Gebreegziabher Gebremedhn; Girmay Fitiwi Lemma (The Pan African Medical Journal, 2017)

(untitled)
INTRODUCTION: globally, increasing consideration has been given to the assessment of patient satisfaction as a method of monitor of the quality of health care provision in the health institutions. Perioperative patient satisfaction has been contemplated to be related with the level of postoperative pain intensity, patients' expectation of the outcome, patient health provider relationship, inpatient services, hospital facilities, access to care, waiting time, cost and helpfulness of treatments received. The study aimed to assess the level of patient satisfaction with perioperative surgical services and associated factors. METHODS: hospital based quantitative cross-sectional study was conducted in University of Gondar teaching hospital from April1-30, 2014. Structured Amharic version questionnaire and checklist used for data collection. All patients who operated upon during the study period were included. Both bivariate and multivariate logistic regression model used to identify the variables which had association with the dependent variable. P-values 0.05 were considered statistically significant. RESULTS: two hundred and seventy eight patients underwent surgery during the study period. Nine patients were excluded due to refusal to participate in the study. A total of 269 out of 278 patients were included in the study with a response rate of 96.8%. The overall level of patient satisfaction with perioperative surgical services was 98.1%. The variables that had association with the outcome variable from the multivariate analysis were patient admission status (AOR=0.073, CI=0.007-0.765, P=0.029), information about the disease and operation (AOR=0.010, CI=0.001-0.140, P=0.001) and operation theatre staff attention to the patients complains (AOR=0.028, CI=0.002-0.390, P=0.008) respectively. CONCLUSION: the level of patient satisfaction with perioperative surgical services was high compared with previous studies conducted in the country and other countries in the world. Health professionals need to give emphasis for information on care provision processes, patients' health progress and patients' complaints.